Building a total quality culture - Batten, Joe (Crisp Pub. Menlo ParkUS, 1992)
Lists 10 basic principles for building a total quality culture. Provides the insights and tools necessary for realizing tough-minded leadership, the qualities, and the performance that characterize a total quality culture.